Development of The Context Clues Method to Improve The Reading Skills of Pre-Service Teachers - Razak, Yusuf; Amiruddin; Inayah, Nur; A, Marya; Asyurah Khas, Suci (Jurnal Pengabdian Kepada Masyarakat Patikala, 2022)
Developing teaching materials for Language Education Study Program students (pre-service teachers) in the academic reading course utilizing the context clues method to improve reading abilities. This community service used is design development through stages that include measurement of needs, literature study, small-scale research, and value considerations, planning (planning), product draft development, development of learning materials, learning process, and evaluation instruments, initial field trials, revising test results, main field trials, product improvement results from field tests, and field implementation tests, final product improvements, dissemination, and implementation. The consequences of using the context clues technique to teach academic reading can help pre-service teachers enhance their critical thinking, analytical, and reading skills.